Accelerated discharging kinetics in zigzag- shaped triplex-tube latent heat storage with nano-modified phase change materials additives - Saleh Al Arni; Hakim S. Sultan Aljibori; Azher M. Abed; Hayder I. Mohammed; Jasim M. Mahdi; Hussein Togun; Abdellatif M. Sadeq; Mohammad Ghalambaz; Nidhal Ben Khedher (Case Studies in Thermal Engineering)
This study explores efficient schemes to substantially accelerate the discharge rates of phase change materials contained in a zigzag-shaped triplex-tube heat exchanger. It comprehensively investigates how zigzag geometry, heat transfer fluid flow parameters, and nanoparticle additives affect PCM discharge characteristics. Introducing a high 67.5° zigzag angle produced a 43.8 W solidification rate, which improves discharge rate by 10.6 % over straight tubes by increasing heat transfer area and promoting vortex formation. Extending the zigzag length to 15 mm further boosted the rate by 61.5 %–157.4 W by expanding the heat exchange surface area. Increasing the Reynolds number of the heat transfer fluid from 250 to 500 enhanced the solidification rate by 26 %–157.4 W by augmenting convective heat transfer. Lowering the heat transfer fluid inlet temperature from 20 °C to 10 °C dramatically reduced solidification time by 75 %, from 1956 s to 774 s by accelerating phase transition kinetics. Furthermore, adding 4 % aluminum oxide nanoparticles improved the rate by 16 %–182 W by enhancing thermal conductivity. Combining optimal parameters (67.5° zigzag angle, 15 mm length, 500 Reynolds number, 10 °C inlet temperature, and 4 % aluminum oxide nanoparticles) achieved a remarkable 300 % increase in discharge rate, from 39.6 W to 198.4 W compared to baseline straight tube configurations with pure phase change material.